Aβ Seeding as a Tool to Study Cerebral Amyloidosis and Associated Pathology - Friesen, Marina; Meyer-Luehmann, Melanie (Frontiers in Molecular Neuroscience, 2019)
Misfolded proteins can form aggregates and induce a self-perpetuating process leading to the amplification and spreading of pathological protein assemblies. These misfolded protein assemblies act as seeds of aggregation. In an in vivo exogenous seeding model, both the features of seeds and the position at which seeding originates are precisely defined. Ample evidence from studies on intracerebral injection of Aβ-rich brain extracts suggests that Aβ aggregation can be initiated by prion-like seeding. In this minireview, we will summarize the past and current literature on Aβ seeding in mouse models of AD and discuss its implementation as a tool to study cerebral amyloidosis and associated pathology.